Development of a customizable Serious Game for scientific dissemination: An approach based on Action Research - Ckagnazaroff, Daniel Duarte; Silvério, Juan Vitor Saar; Nascimento, Júlia; Maia, Pedro Henrique; Silva, Sofia; Oliveira, Maria Clara Gomes Silva de; Souza, Joana Gabriela Ribeiro de; Ishitani, Lucila (Anais do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames); 2025: Anais do XXIV Simpósio Brasileiro de Jogos e Entretenimento Digital, 2025)
Introduction: Games have been used for purposes beyond entertainment with great success. One of these purposes is Scientific Dissemination, utilizing a game’s ludic aspects to engage the general public with scientific research. Objective: This study aims to identify desirable characteristics of customizable Serious Games for purposes of Scientific Dissemination through the development of two minigames and their editors. Methodology or Steps: The Action Research qualitative research methodology was employed due to its “learning by doing” approach, which enables the team to gain a deeper understanding of the target audience’s needs. Results: We developed two customizable games and their editors through two Action Research cycles. This experience enabled the team to identify four desirable characteristics for customizable games used in Scientific Dissemination.